Nilai Pendidikan Islam dalam Animasi Upin Ipin dan Signifikansinya Terhadap Sikap Toleransi Beragama Anak SD - Al Ihwanah (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2019)
Religious life is being disturbed by terror issues in our country. The pros and cons of this problem worsen the atmosphere of religious harmony. Misunderstanding of religious teachings causes intolerance. Therefore, the transformation of the value of Islamic education is an important thing that must be done immediately, especially for children as the next generation of the nation. How to cultivate this attitude of religious tolerance should take into account the characteristics of children, such as he likes fun things. Fun things kids like animated cartoons. Most of the kids love watching animated cartoons of Upin Ipin. This study analyzes the value of Islamic education in Upin and Ipin animation series, and its significance to religious tolerance of children. Based on interviews, field observations, and animated readings, this article argues that this animation teaches a character that matches the value of Islamic education. The values ​​of Islamic education have significance in fostering religious tolerance of children.